(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
There are no numerical research paper attempts to simulate the break-up mechanism of droplets in the spray development. In particular, the work described here refers to study and quantify the break-up of droplets regime and their effects on the spray behavior. With this purpose, the model parameters results, based on droplet break-up model proposed by Reitz and Diwakar [1] and momentum flux calculations are performed. The parameters that are used in the droplet break-up model are stored in the code as properties. These properties are saved in every computation cell. The parameters are Weber number, break-up time and stable droplet diameter. The numerical simulation is implemented as Eulerian-Eulerian approach. The spray moments theory is used for the liquid phase. Finally the study is implemented in a conceptual model to investigate the possible benefits of the droplet break-up model. A good agreement for the numerical results are compared with the experimental data for the spray tip penetration.